Proyecto factibilidad para la Implementación de una microempresa Comercializadora de carne de rana Envasada al vacío en el cantón Zamora, Provincia de Zamora Chinchipe para el año 2016 - Chacha Gordillo, Astrid Carolina (2017)
The general objective of this project is focused on determining the feasibility for the creation of a microenterprise selling frog meat vacuum packed, in Canton Zamora, Province of Zamora Chinchipe, to meet the existing needs in Canton Zamora. In order to develop the specific objectives proposed, it was necessary to use the inductive, descriptive deductive method; as well as the use of techniques such as the survey, observation and bibliography, necessary elements applied for the correct execution of this project. According to the INEC - 2010, there is a total of economically active population in the canton Zamora of 10,757 inhabitants and according to the National Agency for Health Regulation, Control and Surveillance there are 133 establishments that sell products of basic necessity, with this background we proceed to take the sample object of study giving us as a result a sample of 340 and then proceeded to make the respective tabulation of the surveys of both the bidders and applicants to issue the respective analyzes of each of the questions posed. Then the respective market study was carried out to determine the existing demand and supply obtaining that for year one the potential demand is 2,948 family’s, the real demand is 2,746 family’s, the effective demand of 2,691 family’s with a per capita consumption of 62 , 77 giving an effective annual demand of 168,890 pounds and the unsatisfied demand is 150,634 pounds, as also the technical study was considered helping to determine that the maximum capacity for the processing of frog meat in the microenterprise is 140,000 pounds per year, which would reach to cover 93% of the unmet demand for year one in the consumption of frog meat vacuum packed. Continuing with the project, it was strategically determined that for the implementation of the microenterprise its location is in the city of Zamora, Barrio Central, between Diego de Vaca and Pio Jaramillo Alvarado streets, which is a strategic sector and suitable for its implementation. The commercialization process is established within the engineering of the project, where each phase is described from the acquisition of the raw material to its commercialization. The financial study was essential for the development of this project, where it was determined that the total investment required is $ 91,768.71, as well as the income, costs and expenses incurred by the microenterprise for its operation. The financial indicators of the NPV which was 177,601.00, the IRR of 42.32, Benefit Cost of 1.10 and the Capital Recovery of 2,55, that is to say of 2 years, 6 months and 18 days, allowed to determine in a clear manner the feasibility of the project, providing reasonable assurance for decisionmaking, as well as the application of the sensitivity analysis with an increase in costs of 6% or the decrease in revenues of 6%, a positive result of 0,99 was obtained. It concludes by issuing the respective conclusions and recommendations of the project, reaching the conclusion that the project is feasible according to the study applied, and according to the financial indicators that the project gives us.